Implikasi Teknologi Terhadap Pendidikan Islam di Era Globalisasi - Unik Hanifah Salsabila; Avif Ariyanto; Ahmad 'Alim Wijaya; Hafidh Fadillah Aziz; Ardiyan Muhammad Syafii Ma'arif (Wardah, 2022)
Abstract: In this era of globalization, people everywhere, including Indonesia, are deeply impacted by technological advances. Significant advances in information technology have enabled us to quickly access a vast array of content from around the world in this era of globalization. This relates to the study's overall objective, which is to analyze the impact of current technology on Islamic education in a globalizing world. Due to the qualitative nature of this study, information is obtained through a survey of the relevant scholarly literature. Using this approach, authors can discover how technology affects schooling in the age of globalization. This analysis considers the contributions of community culture, materialistic individuals, educational privatization, and technological reliance. In this age of globalization, the education sector faces many challenges. These external causes and problems have both positive and negative effects. However, this permits Islamic schools to advance in sophistication, creativity, and innovation while keeping faithful to Islamic teachings.